Moisture absorption capacity of kenaf fiber-reinforced unsaturated polymer composites and its effect on their mechanical properties - Rashdi, Abdalla A. AB. (2010)
Conventional fiber reinforced composites are composed of carbon and glass fibers, which are incorporated into unsaturated polyester or epoxy resin. These composites show high mechanical and thermal properties, so they are widely used in various applications from aerospace to sports. However, these advantages, on the other hand, cause environmental problems in disposal by incineration. Thus, in order to overcome these problems, environmentally friendly composites such as kenaf are today keenly required by utilizing natural fibers as reinforcements combined with unsaturated polyester as matrices. There are numerous advantages of using Kenaf. Kenaf exhibits low density, non-abrasiveness during processing, high specific mechanical properties, and biodegradability. But natural composites are susceptible moisture when operating in changing environmental conditions. Moisture absorption can result in swelling of the fiber resulting in dimensional stability problems in the lignocellulosic fiber composite. This leads to changes in mechanical properties of the thermoset are known to occur as a result of water absorption. The absorption of moisture by the fibers is minimized in the composites due to encapsulation by the polymer and good fiber-matrix bonding. Most of the moisture studies that have been conducted have focused on water immersion. Fewer studies have examined the effects of relative humidity related to weathering conditions and soil buried. This study concentrate in evaluating the amount of moisture absorption of kenaf unsaturated polyester composites exposed to three different environmental conditions for a certain period of time, and to provide which condition that would be better for kenaf unsaturated polyester engineering applications. Thus moisture absorption due to soil buried, moisture absorption due to water immersion and moisture absorption due to natural weathering were studied, as well as the effect of fibers contents in moisture absorption rate was studied where 10%, 20%, and 30% fiber contents where used. Also the study discuss if the unsaturated polyester can reduce the amount of moisture pick up of the fibers and gives good adhesion to decrease the rate and amount of water absorbed in the interphase region of the composites. Therefore the study will explain the behavior of moisture up-take due to these three conditions and its effects in the mechanical properties of the kenaf unsaturated composites the properties of interest was tensile strength. KFRUPC samples tensile strength and modulus of kenaf fiber reinforced unsaturated polyester composite were carried out using the Instron 5569 Universal Electromechanical Testing System with 50 KN loading capacity. This work employed long kenaf fiber (modified by alkali surface treatment on the fiber with a 6% NaOH solution to improve the adhesion and make them more polar) as reinforcement of the composite. For the matrix resin, unsaturated polyester resin of type Reservol P9509 was used. In this study, kenaf fiber reinforced unsaturated polyester composite (KFRUPC) was made, and their mechanical performances were investigated. This combination of environmental conditions provides a broad overview for most any condition that would be typically seen in an infrastructure application ranging from underwater applications to natural weather environments. The availability of comparable data for the various humidity conditions also provides data that can be used to design test environments to simulate long-term exposure conditions. Finally we can conclude that high fiber content leads to increase in moisture absorption for all environmental conditions. Although with high fiber content slightly better tensile strength were obtained with all environmental conditions. This increase in tensile strength may be due to better mechanical interlocking between fiber and matrix due to the limited swelling of the fiber by low water absorption. Form another point of view the effect of moisture absorption in tensile strength was high in case of water immersion test compare to soil buried and natural weathering tests, where the tensile stress of the KFRUPC drop to 84 MPa, 122 MPa and 134 MPa respectively for the 30%wt fiber content. Natural weathering test case showed that the KFRUPC absorb less moisture and gives high tensile strength compare to soil buried and water immersion tests, which indicate that KFRUPC could be good candidate for outdoor applications.